Evaluation of Education and Training Program during The COVID-19 Pandemic - Wasiah Sufi; Afrizal Afrizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The goal of this study is to assess the Pekanbaru City Environmental and Forestry Center's education and training program. The approach employed in this study was descriptive qualitative data obtained from secondary and primary sources, as well as data analysis utilizing an interactive model, which is an interactive cycle in the sense that qualitative analysis is a continuous, recurring, and ongoing activity. The findings revealed that the evaluation of the implementation of education and training at the Pekanbaru Environmental and Forestry Center during the COVID-19 pandemic was still ongoing and had a fairly good impact on increasing the knowledge and abilities of the training participants, though it was not yet significant because it was conducted online and there were still issues with networking during the training process. Based on the competency assessment's evaluation results.